Exosome therapeutics for COVID‐19 and respiratory viruses. Issue 3 (31st January 2021) - Popowski, Kristen D.; Dinh, Phuong‐Uyen C.; George, Arianna; Lutz, Halle; Cheng, Ke
Abstract: Respiratory viral diseases are a leading cause of mortality in humans. They have proven to drive pandemic risk due to their complex transmission factors and viral evolution. However, the slow production of effective antiviral drugs and vaccines allows for outbreaks of these diseases, emphasizing a critical need for refined antiviral therapeutics. The delivery of exosomes, a naturally secreted extracellular vesicle, yields therapeutic effects for a variety of diseases, including viral infection. Exosomes and viruses utilize similar endosomal sorting pathways and mechanisms, providing exosomes with the potential to serve as a therapeutic that can target, bind, and suppress cellular uptake of various viruses including the novel severe acute respiratory syndrome coronavirus 2. Here, we review the relationship between exosomes and respiratory viruses, describe potential exosome therapeutics for viral infections, and summarize progress toward clinical translation for lung‐derived exosome therapeutics. Abstract : The delivery of exosomes, a naturally secreted extracellular vesicle, yields therapeutic effects for a variety of diseases, including viral infection. Exosomes and viruses utilize similar endosomal sorting pathways and mechanisms, providing exosomes with the potential to serve as a therapeutic that can target, bind, and suppress cellular uptake of various viruses including the novel SARS‐CoV‐2 coronavirus.